RRNA adenine methylation requires T07A9.8 gene as rram-1 in Caenorhabditis elegans. (27th January 2018) - Yokoyama, Wataru; Hirota, Keiko; Wan, Huahua; Sumi, Naoaki; Miyata, Mai; Araoi, Sho; Nomura, Naoto; Kako, Koichiro; Fukamizu, Akiyoshi
Abstract: RNAs are post-transcriptionally modified in all kingdoms of life. Of these modifications, base methylations are highly conserved in eukaryote ribosomal RNA (rRNA). Recently, rRNA processing protein 8 (Rrp8) and nucleomethylin (NML) were identified as factors of N 1 -methyladenosine (m 1 A) modification in yeast 25 S and mammalian 28 S rRNA, respectively. However, m 1 A modification of rRNA is still poorly understood in Caenorhabditis elegans ( C. elegans ). Here, using the liquid chromatography/tandem mass spectrometry analysis and RNA immunoprecipitation assay, we have identified that the m 1 A modification is located around position 674 (A674) of 26 S rRNA in C. elegans . Furthermore, quantitative PCR-based analysis revealed that T07A9.8, a C. elegans homolog of yeast Rrp8 and human NML, is responsible for m 1 A modification at A674 of 26 S rRNA. This m 1 A modification site in C. elegans corresponds to those in yeast 25 S rRNA and human 28 S rRNA. Intriguingly, T07A9.8 is not associated with pre-rRNA transcription under normal nutrient conditions. Since the m 1 A modification of 26 S rRNA requires T07A9.8 in C. elegans, we designated the gene as rR NA a denine m ethyltransferase-1 ( rram-1 ).